Pre-service EFL teachers’ perception on technology-based formative assessment in their teaching practicum - Prastikawati, Entika Fani (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2021)
The spread of the pandemic COVID-19 has made many changes in educational policy such as the assessment in English teaching and learning process. The process and procedures in the assessment need to be adjusted from face-to-face assessment into blended and online assessments. Not only English teachers, pre-service EFL teachers are also required to be ready and adapt to the changes quickly. To adapt it, the integration of technology in the assessment process has been examined. However, the involvement of technology in the area of formative assessment remains underexplored, particularly in the teaching practicum conducted by pre service EFL teachers. The present study is trying to fill the gaps by investigating pre-service EFL teachers’ perception on technology-based formative assessment which is implemented in their teaching practicum. A total of 57 pre-service EFL teachers completed a Likertscale questionnaire. After fulfilling the questionnaires, there were 19 pre-service EFL teachers who agreed and volunteered to be in a semi-structured interview. The findings show that the involvement of technology in formative assessment is perceived positively by pre-service EFL teachers in their teaching practicum during the pandemic COVID-19. They confess that technology has played its practical role in helping them assess their students. Further, the implementation of technology-based formative assessments promotes the students’ performance.